La utilización de los juegos tradicionales y su incidencia en el desarrollo psicomotriz de las niñas y niños de primer año de educación general básica Eloy Alfaro nº 1 de la ciudad de Riobamba, en el período lectivo 2013-2014 - Garcia Tapia, Monica Paulina (2014)
This thesis refers to "THE USE OF TRADITIONAL GAMES AND ITS IMPACT ON DEVELOPMENT PSYCHOMOTOR GIRLS AND CHILDREN FIRST YEAR BASIC EDUCATION GENERAL ELOY ALFARO no.1 CITY Riobamba for school year 2013-2014 ". The general objective was raised for this research was: Analyze how the use of Traditional Games affect the Psychomotor Development of Children First Year of Basic General Education "Eloy Alfaro" Nº 1, Riobamba semester from 2013 to 2014 . Scientific and Statistical Model, Deductive, Inductive, Analytical, Synthetic: methods as were used. The techniques and instruments were: Survey applied to teaching First Year Basic Education General Eloy Alfaro Nº 1, in order to know if the traditional games influence the Psychomotor Development of Children, and see if they carry out areas for cooperation and respect for the rules of coexistence. Ozeretzky test was also applied to assess the psychomotor development of children. Analyzing the results of the applied survey, we found that 100% of the teachers expressed that traditional games if they influence the Psychomotor Development of Children. 100 % of teachers report that the traditional games if allowed to develop spaces for cooperation and respect for the rules of behavior in children. According to test Ozeretsky concluded that 63 % of children have satisfactorily Psychomotor Development, 37% have an unsatisfactory Psychomotor Development.